Easyvs: uma ferramenta para triagem virtual mista baseada em alvo e ligante - Wandré Nunes de Pinho Veloso (2019)
The drug discovery process consists of several steps and the use of computational tools can be an essential part, especially during the early research stages. It is possible, for example, to study large numbers of molecules from various compound libraries from physico-chemical properties or even by predicting the mode and energy of binding between two or more molecules. EasyVS is a web tool developed to simplify the previously described process from the selection of compounds libraries and virtual screening of ligands. With an intuitive interface, this tool allows users to go from the selection of a protein target with known structure, through docking parameterization to its execution and results visualization, in a few clicks. EasyVS also allows users to choose from more than 16 million molecules through ﬁlters based on molecular properties, as well as the grouping through Tanimoto’s similarity index. This tool was used, in a case study, for the virtual screening of ligands for GPCR (G protein coupled receptors) and presented satisfactory results, indicating molecules already known as ligands, separating them from decoys, as well as new potential ligands to be studied. This study proved to be relevant since GPCRs are considered the largest family of targets for approved drugs. We intend to increase the processing capacity of the server availableforEasyVSinordertoreducethecomputationtimeoftherequisitions,besides making viable new functionalities for EasyVS.